Three Economist's Tools for Antitrust Analysis: A Non-Technical Introduction - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2017)
The importance of economics to the analysis and enforcement of competition policy and law has increased tremendously in the developed market economies in the past forty years. In younger and developing market economies, competition law itself has a history of twenty to twenty-five years at most – sometimes much less – and economic tools that have proven useful to competition law enforcement in developed market economies in focusing investigations and in assisting decision makers in distinguishing central from secondary issues are inevitably less well understood. This paper presents a non-technical introduction to three economic tools that have become widespread in competition law enforcement in general and in the analysis of proposed mergers in particular: critical loss analysis, upward pricing pressure, and the vertical arithmetic.
Keywords: 330